2010
DOI: 10.1007/s10517-010-1022-0
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Motor Disorders in 7-Day-Old Rats with Severe Hypoxic-Ischemic Injury of the Brain

Abstract: Seven-day old rats were subjected to unilateral ligation of the common carotid artery followed by 2-h exposure to a gas mixture consisting of 8% oxygen and 92% nitrogen. Locomotor function of rats was monitored weekly. Functional deficit in these animals persisted for at least 3 months. The exercise tests of rotarod, hanging, and narrowing track were most informative. Our results can be used in preclinical studies of new drugs for the therapy of perinatal brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…HIBD caused by asphyxia remains a common cause of numerous types of chronic disability, including cerebral palsy, mental retardation and epilepsy (1,2). HIBD has an incidence of 1–80/1,000, among which 10–20% of patients succumb during the neonatal period (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…HIBD caused by asphyxia remains a common cause of numerous types of chronic disability, including cerebral palsy, mental retardation and epilepsy (1,2). HIBD has an incidence of 1–80/1,000, among which 10–20% of patients succumb during the neonatal period (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of regenerative ability in the central nervous system after injury is considered to be its fundamental cause [2]. HIE can lead to postneonatal neurological sequelae, that is, cerebral palsy, mental retardation, learning disability, and epilepsy [36]. Data from Pakistan has shown that it is one of the leading causes for admission in a neonatal unit [7].…”
Section: Introductionmentioning
confidence: 99%
“…Its pharmacological aspect is limited due to insuffi ciently developed experimental approaches to the search and preclinical study of agents for the development of medicinal products [7].…”
mentioning
confidence: 99%